Digital exercise interventions to improve physical functioning of people with breast cancer: Protocol for a scoping review - Katherine A. Mankelow; Sean O’Connor; Olinda Santin; Nicole E. Blackburn; Iseult M. Wilson (PLoS ONE, 2026)
Introduction Breast cancer incidence rates are rising due to early detection, improved screening methods and advances in treatment options. As mortality rates reduce, there is a growing population living longer with treatment side-effects who require assistance. Prevalent issues arising after breast cancer treatment include pain, fatigue, lymphoedema and arm and shoulder mobility issues. Evidence demonstrates that upper limb exercises help reduce these common side effects and improve day-to-day functioning and quality of life. However, access to physiotherapy and rehabilitation services remains limited due to resource and access constraints. Despite a growing interest in digital health resources, little is known about the effectiveness of using digital exercise interventions to help resolve this problem. Methods and analysis A scoping review of available literature will be undertaken to explore what digital or online prehabilitation or rehabilitation interventions exist for people with breast cancer that incorporate an exercise component aimed at improving physical function or mobility. Peer-reviewed studies in English will be eligible for inclusion. A systematic search of Medline ALL, Embase, CINAHL, and Web of Science will be conducted and any relevant grey literature form trusted sources will also be included in our review. The Arksey and O’Malley framework will be applied together with updated guidance from other authors. To enhance rigour, the Joanna Briggs Institute methodology for scoping reviews will also be used to ensure accurate reporting. Articles will be screened by title and abstract against eligibility criteria before independent full text screening by two researchers. Arising conflicts will be resolved by consulting a third reviewer. To summarise the available evidence, data will be extracted using a tailored charting template and a descriptive narrative synthesis will follow. Ethics and dissemination As this research involves the analysis of already published, peer-reviewed literature, ethical approval is not required. The results of this scoping review will be submitted for publication in a peer-reviewed journal. Any significant deviations from the original protocol will be transparently reported and justified.